Bio-systematic Studies on Cotugnia tetragona Sp. Nov. (Cestoda: Davaineidae) from Columba livia - Bhure1, S.S. Nanware1*, R.M. Dhondge2 and D.B. (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">The present investigation deals with a new species of the genus Cotugnia [1] from the intestine of Columba livia, district Nanded, (M.S.) of India. The new species Cotugnia tetragona is comes closer to all the known species of the genus Cotugnia in general topography of organ but differs due to scolex tetragonal, four rounded suckers, rostellum large, oval, rectangular with 120-130 rostellar hooks, mature segments broader than long, testes 60-70 in numbers, oval to rounded and post-ovarian, cirrus pouch elongated, cirrus thin lie within cirrus sac, vas deferens short, coiled tube, upward directed, genital pore marginal at both side in the middle of segment, vagina posterior to cirrus pouch, receptaculum seminis present, ootype small, vitelline gland large, compact.